Evaluasi lanskap koridor Sungai Sekadau di Desa Mungguk, Sekadau, Kalimantan Barat - Selly, Crismania Apriati; Alfian, Rizki; Budiyono, Debora (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021, 2021)
A river is a natural water flow that flows from upstream to downstream. Sekadau River is located in the middle of Sekadau city to be precise in Mungguk Village, the center of urban growth. The existence of a river flow that crossed the city made many changes occurring in the Sekadau River corridor, this was due to the large number of settlements in the riverbank area which resulted in a decrease in river water quality. The purposes of this study were to analyze landscape conditions, prepare recommendations based on SWOT analysis and spatial analysis. The method used in this research was descriptive qualitative with analysis methods, namely SWOT analysis and spatial analysis. The result of this study, based on a SWOT analysis, showed that there was community-based management in coordination with the government, the community and the private sector. Spatial analysis showed that the land cover of the Sekadau River was still dominated by vegetation along the riverbanks, but the problem was in the estuary which had become a settlement. At the bottom of the river, there was a stepping stone corridor, in the middle there was a linear corridor and at the top of the river there was a linear corridor.